John Bull ground down. - [F.L.] (Humphrey, H., 1795)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; John Bull (Symbolic character); Pitt, William, 1759-1806; Burke, Edmund, 1729-1797; Great Britain -- Politics and government -- 1760-1820 -- Caricatures and cartoons